INFLUENCIA DE LA AUTOEFICACIA EN EL ÁMBITO ACADÉMICO - Ruiz Dodobara, Fernando (2005)
Believing in the own capacity or self- effectiveness in certain situations could be considered as a vital concept within the academic field because it can better predict performance than otherwise personal skills and knowledge can do.This concept is inserted within Bandura’s Cognitive Social Theory, which considers the human being as a self-organized, self-reflexive and task-committed individual. A key point in this theory is that people have personal believes regarding their self- effectiveness that allow them to have a certain control on their feelings, actions and thoughts. This means that individuals’ behavior can be influenced by what they think, create and feel. Therefore, self- effectiveness becomes a good predictive of the human behavior. Self- effectiveness believes also have an influence in the way each person acts through cognitive, motivational, affective and selective processes. In the academic field specifically, self- effectiveness believes have an impact on student’s motivation, persistence and academic success. It is worth to mention, also, that teacher’s self- effectiveness believes about their work have an important influence in the student’s performance. Finally, we can say that between the self- effectiveness sources, we found: the successful use of experiences, the comparison with similar models, the social persuasion and the corporal states.